Search for a meteoritic component within the impact melt rocks of the Chicxulub impact structure peak ring, Mexico. (15th April 2022) - Feignon, Jean-Guillaume; Schulz, Toni; Ferrière, Ludovic; Goderis, Steven; de Graaff, Sietze J.; Kaskes, Pim; Déhais, Thomas; Claeys, Philippe; Koeberl, Christian
Abstract: Constraining the degree of preservation of a meteoritic signature within an impact structure provides vital insights in the complex pathways and processes that occur during and after an impact cratering event, providing information on the fate of the projectile. The IODP-ICDP Expedition 364 drilling recovered a ∼829 m continuous core (M0077A) of impactites and basement rocks within the ∼200-km diameter Chicxulub impact structure peak ring. No highly siderophile element (HSE) data have been reported for any of the impact melt rocks of this drill core to date. Previous work has shown that most Chicxulub impactites contain less than 0.1% of a chondritic component. Only few impact melt rock samples in previous drill cores recovered from the Chicxulub might contain such a signal. Therefore, we analyzed impact melt rock and suevite samples, as well as pre-impact lithologies of the Chicxulub peak ring, with a focus on the HSE concentrations and Re–Os isotopic compositions. Similar to the concentrations of the other major and trace elements, those of the moderately siderophile elements (Cr, Co, Ni) of impact melt rock samples primarily reflect mixing between a mafic (dolerite) and felsic (granite) components, with the incorporation of carbonate material in the upper impact melt rock unit (from 715.60 to 747.02 meters below seafloor). The HSE concentrations of the impact melt rocks and suevites are generally low (<39 ppt Ir, <96 ppt Os, <149 ppt Pt), comparable to the values of the average upper continental crust, yet three impact melt rock samples exhibit an enrichment in Os (125–410 ppt) and two of them also in Ir (250–324 ppt) by one order of magnitude relative to the other investigated samples. The 187 Os/ 188 Os ratios of the impact melt rocks are highly variable, ranging from 0.18 to 2.09, probably reflecting heterogenous target rock contributions to the impact melt rocks. The significant amount of mafic dolerite (mainly ∼20–60% and up to 80–90%), which is less radiogenic ( 187 Os/ 188 Os ratio of 0.17), within the impact melt rocks makes an unambiguous identification of an extraterrestrial admixture challenging. Granite samples have unusually low 187 Os/ 188 Os ratios (0.16 on average), while impact melt rocks and suevites broadly follow a mixing trend between upper continental crust and chondritic/mantle material. Only one of the investigated samples of the upper impact melt rock unit could also be interpreted in terms of a highly diluted (∼0.01–0.05%) meteoritic component. Importantly, the impact melt rocks and pre-impact lithologies were affected by post-impact hydrothermal alteration processes, probably remobilizing Re and Os. The mafic contribution, explaining the least radiogenic 187 Os/ 188 Os values, is rather likely. The low amount of meteoritic material preserved within impactites of the Chicxulub impact structure may result from a combination of the assumed steeply-inclined trajectory of the Chicxulub impactor (enhanced vaporization, and incorporation of projectile material within the expansion plume), the impact velocity, and the volatile-rich target lithologies.